The effects of parental care and autonomy on adolescents’ emotion Dysregulation in Peninsular Malaysia - Nur Afrina Rosharudin,; Suzana Mohd Hoesni,; Noor Azimah Muhammad,; Manisah Mohd Ali, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Parents are important figures in shaping an adolescent’s emotion regulation. However, there have been fewer studies investigating the effects of parental care and parental autonomy on adolescents’ emotion regulation, and the findings from the existing research have been inconsistent. Therefore, the aim of this study is to examine the effects of parental care and autonomy (from both the father and mother) on adolescents’ emotion dysregulation. The Malay versions of Parental Bonding Instrument (PBI) and Difficulties in Emotion Regulation Scale-18 (DERS-18) were administered to 491 students between the ages of 13 and 14 years old. The students were recruited from public schools in Peninsular Malaysia by using a non-proportionate random stratified sampling technique. This study employed the Structural Equation Modelling (SEM) with regression analysis. The results showed a significant negative effect of paternal and maternal care on adolescent’s emotion dysregulation. There is no significant effect of paternal and maternal autonomy on the adolescent's emotion dysregulation. This study concludes that both fathers and mothers who care for and provide warmth to their children would promote better emotion regulation. The current findings highlight intervention and prevention efforts in promoting parental care and warmth in our children upbringing particularly involving adolescents. These will foster positive impact in the adolescents’ abilities to regulate their emotion.